Satapang Beauty (Produk Sabun Talas Jepang/Satoimo) - Nurbaya Busthanul; Jumriah Langkong; Anwar Hardiyanti; Nawir A. Fathanul; Khatimah Husnul; Sakia Nurul; Fadhilah Nur (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2019)
Japanese taro (Satoimo) is one type of plant rich in carbohydrate content, which is good for human health. Therefore, this food crop is also a staple food of Japanese society, because it is believed to provide very good benefits for the body. In Indonesia, nowadays there have been a lot of Japanese taro or satoimo cultivation. In addition to the content contained in Japanese taro plants for health benefits, Japanese taro can also be processed into a variety of products, such as chips, juice, ice cream, dry pastries, croquettes, pudding, handbody, shampoo, and soap products that are all made from satoimo. In addition to having a good content if consumed, Japanese taro is also useful for beauty ingredients. Armed with knowledge and creativity, students are inspired to create a business unit that produces Japanese taro-based soap. It is hoped that through the support of the supervisor, it will be integrated into an Entrepreneurial Student Program (PMW-Unhas) and this business is expected to grow and develop. The problem is how students sharpen their talents and interests as entrepreneurs, understand and take advantage of market opportunities for these products. The objectives of making this business are: (1) building soft skills or entrepreneurial character; (2) develop new entrepreneurs who are highly educated and have the mindset of creating jobs; (3) encourage the growth, development or formation of institutions (units / centers) for managing entrepreneurship programs in universities. The method of implementation includes: (1) revealing the ability of human resources, especially in the founders and business actors; (2) delivering information material through social media about matters relating to Japanese taro and satoimo soap; (3) disclosing the development of production and potential supporting factors for increasing production and improving the quality of satoimo soap products. The assistance results show that, (1) Human resources founding the satoimo soap innovator have decent potential and strong motivation in running the business, even though they are still students; (2) Japanese taro-based products can serve as a place to introduce products and can be channeled through various social media so that it is very important as information for the community; (3) This business venture begins to experience growth and is known by the community. The characteristics of Japanese taro as one of the basic ingredients in making natural soaps are rich in nutrients and nutrients that are good for health and the body. It can be concluded that producing Japanese taro satoimo soap is very potential to be developed.Keywords: Satoimo Soap, Talas Japan, PKM-CSR